Reading the natural world in the Middle Ages and the Renaissance perceptions of the environment and ecology - Willard, Thomas (Brepols, 2020)
From the late 600s to the early 1600s, medieval and early modern people engaged with nature in ways that shaped their sense of place, religion, literature, art, and more. Contributors to this volume draw from recent trends in ecological thinking to reassess their chosen topics.00The environment - together with ecology and other aspects of the way people see their world - has become a major focus of pre-modern studies. The thirteen contributions in this volume discuss topics across the millennium in Europe from the late 600s to the early 1600s. They introduce applications to older texts, art works, and ideas made possible by relatively new fields of discourse such as animal studies, ecotheology, and Material Engagement Theory. From studies of medieval land charters and epics to the canticles sung in churches, the encyclopedic natural histories compiled for the learned, the hunting parks described and illustrated for the aristocracy, chronicles from the New World, classical paintings from the Old World, and the plays of Shakespeare, the authors engage with the human responses to nature in times when it touched their lives more intimately than it does for people today, even though this contact raised concerns that are still very much alive today.
Aus der Einleitung: "The essays collected here were first presented as papers at the twenty-fourth annual conference of the Arizona Center for Medieval and Renaissance Studies, held in February 2018."
Keywords: Geschichte 500-1500; Bildliche Darstellung; Fiktionale Darstellung; Umwelt; Konferenzschrift -- 2018 -- Phoenix, Ariz.